ANALISA PERFORMA SEISMIC MERU (STRUKTUR BERTINGKAT PAGODA KHAS BALI): PRELIMINARY STUDY - I Putu Ellsa Sarassantika; Ida Bagus Gede Parama Putra; Sudarno P Tampubolon; I Gede Dhana Putra Sanjaya (Jurnal Rekayasa Teknik Sipil dan Lingkungan - CENTECH, 2023)
The Meru, a multi-tiered Balinese pagoda in Bali, Indonesia, is investigated for its earthquake-resistant properties in this study. Despite the fact that its upper tier is made of timber frames and panels, and its lower tier is made of masonry walls, the Meru has not suffered significant earthquake damage since its construction in 1968. This paper investigates the Meru's architectural form, structural system, building materials, and dynamic responses to seismic activity. The study focuses on an eleven-tier Meru in the Ulun Danu Batur Temple Kintamani Region, Bali Province, and investigates earthquake resistance using a 2-D Finite Element model and Nonlinear time history dynamic analysis method. The results show that the Meru can withstand the maximum credible earthquake for 2500 years, and the Meru's natural periods and modes have been determined. This study is a preliminary investigation into predicting and monitoring the Meru structure's behavior during earthquakes. To further validate the analysis model, future research could include experimental analysis of both individual components and the overall structure.